Leishmania mexicana induces limited recruitment and activation of monocytes and monocyte-derived dendritic cells early during infection. - Patricia M Petritus; Daniel Manzoni-; Ciara Gimblet; Claudia Gonzalez Lombana; Phillip Scott (Public Library of Science (PLoS), 2012)
While C57BL/6 mice infected in the ear with L. major mount a vigorous Th1 response and resolve their lesions, the Th1 response in C57BL/6 mice infected with L. mexicana is more limited, resulting in chronic, non-healing lesions. The aim of this study was to determine if the limited immune response following infection with L. mexicana is related to a deficiency in the ability of monocyte-derived dendritic cells (mo-DCs) to prime a sufficient Th1 response. To address this issue we compared the early immune response following L. mexicana infection with that seen in L. major infected mice. Our data show that fewer monocytes are recruited to the lesions of L. mexicana infected mice as compared to mice infected with L. major. Moreover, monocytes that differentiate into mo-DCs in L. mexicana lesions produced less iNOS and migrated less efficiently to the draining lymph node as compared to those from L. major infected mice. Treatment of L. mexicana infected mice with α-IL-10R antibody resulted in increased recruitment of monocytes to the lesion along with greater production of IFN-γ and iNOS. Additionally, injection of DCs into the ear at the time of infection with L. mexicana also led to a more robust Th1 response. Taken together, these data suggest that during L. mexicana infection reduced recruitment, activation and subsequent migration of monocytes and mo-DCs to the draining lymph nodes may result in the insufficient priming of a Th1 response.